2017
DOI: 10.1212/wnl.0000000000003587
|View full text |Cite
|
Sign up to set email alerts
|

Acute plasma tau relates to prolonged return to play after concussion

Abstract: Objective:To determine whether tau changes after sport-related concussion (SRC) relate to return to play (RTP).Methods:Collegiate athletes underwent preseason plasma sampling and cognitive testing and were followed. After a SRC (n = 46), athletes and controls (n = 37) had sampling at 6 hours, and at 24 hours, 72 hours, and 7 days after SRC. A sample of 21 nonathlete controls were compared at baseline. SRC athletes were grouped by long (>10 days, n = 23) and short (≤10 days, n = 18) RTP. Total tau was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
91
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 35 publications
12
91
1
Order By: Relevance
“…These results indicate that within this cohort, tau‐related changes were in part associated with the presence of PTSD. This finding supports evidence from studies of civilians and athletes that has demonstrated acute elevations in tau related to poor recovery, as shown by higher levels of neurological symptoms and deficits (Bogoslovsky et al., ; Gill et al., ). Participants with an mTBI and concurrent PTSD were, on average, 58.5 months postinjury, indicating that their reported PTSD symptoms were chronic in nature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results indicate that within this cohort, tau‐related changes were in part associated with the presence of PTSD. This finding supports evidence from studies of civilians and athletes that has demonstrated acute elevations in tau related to poor recovery, as shown by higher levels of neurological symptoms and deficits (Bogoslovsky et al., ; Gill et al., ). Participants with an mTBI and concurrent PTSD were, on average, 58.5 months postinjury, indicating that their reported PTSD symptoms were chronic in nature.…”
Section: Discussionsupporting
confidence: 87%
“…Tau is a microtubule‐associated protein that can become hyperphosphorylated, disrupting microtubule organization and creating neurofibrillary tangles (NFTs). Elevated tau concentrations have been reported in both military personnel following blunt force trauma and blast exposures (Gill et al., ; Olivera et al., ) and in athletes following concussive and subconcussive impacts (Gill, Merchant‐Borna, Jeromin, Livingston, & Bazarian, ). Higher tau concentrations in peripheral blood have also been correlated with prolonged return to play in athletes (Gill et al., ).…”
mentioning
confidence: 99%
“…10 Similar to neuroimaging techniques, blood biomarker technology has evolved to be able to detect neural factors at a femtomolar concentration. Among the many potential biomarkers for brain injury, Tau, neurofilament-light (NfL), and glial fibrillary acidic protein (GFAP) have shown their superior ability to predict concussion recovery time, 11,12 cumulative subconcussive axonal damage, [13][14][15] and absence of intracranial bleeding. [16][17][18] However, the relationships between DTI/NODDI metrics and blood biomarkers in reflecting cumulative neural stress from football head impacts have never been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The other indicators of ongoing neuropathology after a concussion are biomarkers such as plasma tau changes (Gill, Merchant‐Borna, Jeromin, Livingston, & Bazarian, ) or white matter changes (Narayana, ). Recently, Kraus et al.…”
Section: Introductionmentioning
confidence: 99%
“…The other indicators of ongoing neuropathology after a concussion are biomarkers such as plasma tau changes (Gill, Merchant-Borna, Jeromin, Livingston, & Bazarian, 2017) or white matter changes (Narayana, 2017). Recently, Kraus et al (2016) have shown that the midbrain electrophysiological responses of concussed athletes reflect impaired auditory processing (Kraus, Anderson, White-Schwoch, Fay, & Popper, 2017).…”
Section: Introductionmentioning
confidence: 99%